Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1007/s003600050198
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation during swimming and diving in bottlenose dolphins, Tursiops truncatus

Abstract: Heat transfer from the periphery is in important thermoregulatory response in exercising mammals. However, when marine mammals submerge, peripheral vasoconstriction associated with the dive response may preclude heat dissipation at depth. To determine the effects of exercise and diving on thermoregulation in cetaceans, we measured heat flow and skin temperatures of bottlenose dolphins (Tursiops truncatus) trained to follow a boat and to dive to 15 m. The results demonstrated that skin temperatures usually rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…Such a variable dive response raises questions about the management of blood gases during submergence. Although there is a premium to conserve oxygen through bradycardia and an associated redistribution of blood flow (Scholander, 1940;Irving et al, 1941;Harrison and Tomlinson, 1960;Elsner, 1965;Elsner et al, 1966), heart rate varies with the intensity of underwater behaviors (Figs4, 5), as does peripheral blood flow, as evident from changes in skin temperature and heat flow from the extremities of diving dolphins Noren et al, 1999). Rather than a hindrance to diving, alterations in blood flow (as facilitated by alterations in heart rate) throughout submergence theoretically facilitate more effective unloading of endogenous oxygen stores by enabling the parallel depletion of the blood and muscle oxygen reserves .…”
Section: Discussionmentioning
confidence: 99%
“…Such a variable dive response raises questions about the management of blood gases during submergence. Although there is a premium to conserve oxygen through bradycardia and an associated redistribution of blood flow (Scholander, 1940;Irving et al, 1941;Harrison and Tomlinson, 1960;Elsner, 1965;Elsner et al, 1966), heart rate varies with the intensity of underwater behaviors (Figs4, 5), as does peripheral blood flow, as evident from changes in skin temperature and heat flow from the extremities of diving dolphins Noren et al, 1999). Rather than a hindrance to diving, alterations in blood flow (as facilitated by alterations in heart rate) throughout submergence theoretically facilitate more effective unloading of endogenous oxygen stores by enabling the parallel depletion of the blood and muscle oxygen reserves .…”
Section: Discussionmentioning
confidence: 99%
“…Thermal windows in permanently submerged marine mammals are found in peripheral body sites such as flukes and dorsal fins of cetaceans (Kanwisher and Ridgway, 1983;McGinnis et al, 1972;Meagher et al, 2002;Noren et al, 1999). These body sites protrude from the streamlined body so that thermal conduction and convection become the most effective heat-transfer mechanisms while diving and swimming.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in marine mammals, this term has often been used referring to the appendages as poorly insulated body regions protruding from the streamlined body (e.g. Meagher et al, 2002;Noren et al, 1999). However, the Thermal windows in seals early observations of Krumbiegel (1933) and Øritsland (1968) might characterise thermal windows in seals more broadly as body surfaces functioning as temporary heat dissipaters during heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…2 Noren et al (1999) showed that ∆T remained at around 1 o C for T W values between 28 o and 31 o C with a linear association. It is noteworthy that these results are in accordance with the values predicted by equation 10, despite the lack of experimental evidence for cold-water conditions.…”
Section: Iterative Proceduresmentioning
confidence: 90%
“…While fur seals may present skin temperatures more than 20 o C above that of ambient water (Boyd, 2000), bare-skinned dolphins have surface temperatures usually within 1 o C of the water even after exercise in warm waters (Noren et al, 1999). Different models have been used to estimate heat exchange in marine mammals (Innes, 1986;Kshatriya & Blake, 1988;Ryg et al, 1988;Hokkanen, 1990;Watts et al, 1993), but the results vary widely, which is probably explained by the practical difficulties entailed in measuring body surface temperature of these animals.…”
Section: Introductionmentioning
confidence: 99%